Determinants and influencing mechanism of outpatient satisfaction: a survey on tertiary hospitals in the People’s Republic of China - Yu, Wenya (Patient Prefer Adherence, 2016)
OBJECTIVE: Most patients in the People’s Republic of China prefer tertiary hospitals when seeking medical services. The aim of this study was to assess outpatient satisfaction with tertiary hospitals in the People’s Republic of China, test overall and subscale satisfaction, and explore whether sociodemographic characteristics lead to different degrees of satisfaction and whether subscale outpatient satisfaction contributes to overall satisfaction. METHODS: A closed questionnaire was given out to investigate outpatients’ sociodemographic characteristics, overall satisfaction, and various subtypes of satisfaction, and a 5-point Likert scale was employed to measure the degree of outpatient satisfaction. Descriptive analysis, Kruskal–Wallis test, Spearman’s rank correlation coefficient, and logistic regression analysis were employed for statistical analysis. RESULTS: Response rate was 92.48% (971/1,050). Outpatients’ sociodemographic characteristics (including sex, age, occupation, monthly income, residence, and marital status) were related to various subtypes of satisfaction to varying degrees. Outpatients who were male, older, married, with low or middle incomes, living in Shanghai or other areas of the People’s Republic of China, medical staff, or students were more satisfied with various subtypes of satisfaction than those without these characteristics. In further analyses, satisfaction with their medical needs being met by doctors had the strongest relation to overall satisfaction, followed by satisfaction with doctors’ service attitudes, medical costs, waiting time, prescription, and diagnosis and treatment time. Satisfaction with environment had the weakest contribution to overall satisfaction. CONCLUSION: This study gave some suggestions for tertiary hospitals in advanced areas of the People’s Republic of China. Outpatient sociodemographic characteristics should be paid more attention by medical staff to improve the degree of satisfaction. Tertiary hospitals in the People’s Republic of China should provide more support on the management of doctors, medical costs, and time.